Performance-Based Budgeting and Regional Financial Performance: The Role of Productive Expenditure and Accountability - Rischa Inung Fauziah; Fandi Galang Wicaksana; Desiana Rachmawati; Richatul Jannah; Kurniana Sandra Lungit (Institut Agama Islam Negeri Kerinci, 2026)
Purpose: This study examines the relationship between Performance-Based Budgeting (PBB) and regional financial performance, with a particular focus on the role of productive expenditure and accountability. Design/Methodology/Approach: This research adopts a quantitative approach using panel data from 33 local governments in Central Java Province over the period 2022–2024, resulting in 99 observations. Productive expenditure is used as a proxy for outcome-oriented budget allocation, while accountability is measured using the Government Institution Performance Accountability System (SAKIP) score. Data were analyzed using panel regression techniques. Findings: The results reveal that productive expenditure has a significant negative effect on regional financial performance, indicating that increased allocation toward capital or outcome-based spending does not necessarily improve financial outcomes due to inefficiencies in budget execution, particularly in procurement processes. In contrast, accountability, as proxied by SAKIP scores, does not show a significant effect, suggesting that accountability practices remain largely procedural rather than performance-driven. Additionally, government size as a control variable has a significant positive impact on financial performance. Research Implications: These findings highlight the need for local governments to strengthen managerial capacity, improve budget execution mechanisms, and enhance substantive accountability practices to ensure that performance-based budgeting achieves its intended outcomes.